EFFECT OF TAX AMNESTY POLICY, KNOWLEDGE OF TAXATION AND SERVICES OF TAX AUTHORITIES ON TAXPAYERS COMPLIANCE: EMPIRICAL STUDY ON SATURN SERVICE OFFICE PAJAK PRATAMA TAX YEAR 2012-2016 - Suak, Meilivia M. G (Universitas Sam Ratulangi, 2019)
Tax has an important role in the source of state revenue, because the largest income of the State comes from the tax sector. The importance of tax compliance ( tax compliance ) in increasing tax receipts and/or tax ratio has encouraged the conduct of research on the determinants or factors that affect compliance. tax is the policy of tax amnesty, knowledge of taxation, and service of tax authorities. This study aims to analyze the effect of tax amnesty policy , knowledge of taxation, and tax authorities services on taxpayer compliance, empirical studies at the Pratama Tax Office Manado Tax Year 2012-2016. The questionnaire was distributed to 42 respondents and in the process with multiple linear analysis methods with SPSS version 22. This study consisted of dependent variables and independent variables. The dependent variable is taxpayer compliance, while the independent variable is the tax amnesty policy, knowledge of taxation, and service of tax authorities. The results showed that the tax amnesty policy did not have a positive and insignificant effect on taxpayer compliance, tax knowledge did not have a positive and insignificant effect on taxpayer compliance, tax authorities' services had a positive and significant effect on taxpayer compliance.